2016
DOI: 10.1039/c5fo00975h
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic-rich lychee (Litchi chinensis Sonn.) pulp extracts offer hepatoprotection against restraint stress-induced liver injury in mice by modulating mitochondrial dysfunction

Abstract: The pulp from lychee, a tropical to subtropical fruit, contains large quantities of phenolic compounds and exhibits antioxidant activities both in vitro and in vivo. In the present study, we investigated the mechanisms underlying the hepatoprotective effects of lychee pulp phenolics (LPPs) against restraint stress-induced liver injury in mice. After 18 h of restraint stress, increased levels of serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activities were observed. High levels of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 45 publications
3
32
0
Order By: Relevance
“…However, it has been proposed that other isolated active compounds in addition to those mentioned above should be included when evaluating the intracellular formation of reactive oxygen species, mitochondrial membrane potential, and changes in cell nuclei morphology in in vitro models. However, the use of all of these compounds may not be practical for routine testing because of the high cost of their inclusion in the monitoring of the hepatoprotective activities of all plant extracts [4447]. …”
Section: Discussionmentioning
confidence: 99%
“…However, it has been proposed that other isolated active compounds in addition to those mentioned above should be included when evaluating the intracellular formation of reactive oxygen species, mitochondrial membrane potential, and changes in cell nuclei morphology in in vitro models. However, the use of all of these compounds may not be practical for routine testing because of the high cost of their inclusion in the monitoring of the hepatoprotective activities of all plant extracts [4447]. …”
Section: Discussionmentioning
confidence: 99%
“…Through a series of enzymatic reactions, intracellular antioxidant enzymes convert reactive radicals into less active radicals (Wen et al, 2015b). For example, SOD can catalyse the dismutation of highly active intracellular superoxide anion O2 − into O2 and hydrogen peroxide (H2O2), which is less active; CAT and GSH-Px can reverse the conversion of H2O2, which could be converted into more detrimental radicals, like hydroxyl radials (·OH), changing the H2O2 generated within cells to H2O and O2, thereby protecting cells from oxidative stress (Halliwell, 2012;Su et al, 2016). Furthermore, antioxidants including phenolics might decrease the cellular level of free radicals indirectly either by inhibiting the activity or expression of free radicals generating enzymes, like NAD(P)H oxidase and xanthine oxidase (XO) or by protecting the activity or expression of intracellular antioxidant enzymes, such as SOD, GSH-Px, and CAT (Lue et al, 2010;Wen et al, 2015b).…”
Section: Antioxidant Capacitymentioning
confidence: 99%
“…More recently, analysis by reverse-phase preparative HPLC has revealed that the three-polyphenol components with major antioxidant activity in Litchi pulp fraction were quercetin 3-rut-7-rha, rutin, and epicatechin [ 26 ]. Phenolic-rich Litchi pulp extracts administered at a dosage of 200 mg/kg/day for 3 consecutive weeks have been also shown to protect in vivo the liver against restraint stress-induced damage by increasing the activity of free radicals scavenger enzymes (glutathione peroxidase, superoxide dismutase, catalase) and reducing mitochondrial reactive oxygen species (ROS) production [ 27 ].…”
Section: Antitumor Properties Of Litchi Pulp-derived Componentsmentioning
confidence: 99%